Effect of digital nutrition education via WhatsApp and mHealth on maternal nutrition literacy and child feeding practices: A systematic review - Fathimah Az Zahra Faiq; Nia Novita Wirawan; Fajar Ari Nugroho (AcTion: Aceh Nutrition Journal, 2026)
Suboptimal infant and young child feeding practices remain a major contributor to child malnutrition, particularly in low- and middle-income countries (LMICs). Maternal nutritional literacy plays a key role in shaping appropriate feeding behaviors. Digital platforms, such as WhatsApp and mobile health (mHealth) applications, have emerged as potential tools for delivering nutrition education. This systematic review followed the PRISMA 2020 guidelines. PubMed, Scopus, and Google Scholar were searched for studies published between 2020 and 2025. Eligible studies included digital nutrition education interventions targeting mothers of infants and young children and reported outcomes related to maternal nutrition literacy and/or child feeding practices. Due to the heterogeneity of the study designs and outcome measures, the findings were synthesized narratively. Fourteen studies were included in the review. Most were conducted in LMIC settings and involved WhatsApp-based or mobile health interventions. Digital education is generally associated with improved maternal nutrition literacy, dietary diversity, timely initiation of complementary feeding, and feeding frequency. Theory-based and interactive interventions have demonstrated stronger engagement than passive approaches. Digital nutrition education via WhatsApp and mHealth shows promising evidence for supporting maternal nutrition literacy and child feeding practices, although methodological variability warrants cautious interpretation.